Exploring Self-Efficacy among Senior High School Students Facing Academic Challenges - Nagita Marva Sasikirana; Fitrania Maghfiroh; Adiwignya Nugraha Widhi Harita (International Conference on Psychology and Education (ICPE), 2025)
This study aims to provide a descriptive overview of self-efficacy among twelfth-grade students who are facing intense academic demands and transition challenges. Self-efficacy, defined as an individual’s belief in their capability to organize and execute actions required to manage prospective situations, plays a critical role in determining students’ motivation and perseverance. A quantitative descriptive approach was employed with 119 students as respondents. Data were collected using a self-efficacy scale comprising items that measure level, generality, and strength dimensions. The findings show that the majority of students have moderate to high self-efficacy, which implies readiness to face academic tasks. Descriptive statistics further reveal variations between class groups. This study highlights the importance of promoting strategies that maintain and enhance students’ confidence in their academic capabilities.